2014
DOI: 10.1007/s13277-014-2042-6
|View full text |Cite
|
Sign up to set email alerts
|

ncRuPAR inhibits gastric cancer progression by down-regulating protease-activated receptor-1

Abstract: ncRuPAR is a newly discovered long noncoding RNA molecule that can upregulate protease-activated receptor-1 (PAR-1) during embryonic growth; however, its role in cancer has not been elucidated. Here, we conducted a study to investigate the role of ncRuPAR in gastric cancer. Significant downregulation of ncRuPAR was detected in gastric cancer tissues compared with paired adjacent nontumor tissues; however, both PAR-1 and vascular endothelial growth factor (VEGF) messenger RNA (mRNA) levels were significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…For example, decreased expression of ncRuPAR significantly correlates with tumor invasion depth, lymph node metastasis, distant metastasis, tumor size and TNM stage in gastric cancer. 95 A downregulation in the expression of AI364715, 96 GACAT1, 97 and GACAT2 98 in gastric cancer tissues; PCAT29 in prostate cancer 99 ; AC026166.2-001 and RP11-169D4.1-001 in larynx squamous cell carcinoma 100 ; lncRNA-LET 101 and MEG3 86 in GBC tissues could also be used as a prognostic marker. The epigenetic changes in lncRNAs could also predict prognosis of the disease.…”
Section: Lncrnas In Cancer Prognosismentioning
confidence: 99%
“…For example, decreased expression of ncRuPAR significantly correlates with tumor invasion depth, lymph node metastasis, distant metastasis, tumor size and TNM stage in gastric cancer. 95 A downregulation in the expression of AI364715, 96 GACAT1, 97 and GACAT2 98 in gastric cancer tissues; PCAT29 in prostate cancer 99 ; AC026166.2-001 and RP11-169D4.1-001 in larynx squamous cell carcinoma 100 ; lncRNA-LET 101 and MEG3 86 in GBC tissues could also be used as a prognostic marker. The epigenetic changes in lncRNAs could also predict prognosis of the disease.…”
Section: Lncrnas In Cancer Prognosismentioning
confidence: 99%
“…LncRNAs which play tumor-suppressorlike roles were found successively, such as FER1L4 [54], ncRuPAR [57], uc001lsz [49] and MEG3 [56]. They downregulated in GC tissues compared with paired normal tissues and their downregulations were associated with larger tumor size, advanced pathologic stage, more vessel or nerve invasion, more lymphatic and distant metastasis or poorer disease-free survival and overall survival.…”
Section: Tumor Suppressor Lncrnasmentioning
confidence: 99%
“…Perineural invasion (tissue level), invasion and lymphatic metastasis (plasma level) [55] MEG3 Tissue Down Tumor size, invasion depth, TNM stage and poor prognosis [56] ncRuPAR Tissue Down Tumor size, invasion depth, lymph node metastasis, distant metastasis and TNM stage [57] BM742401 Tissue Down Poor survival [18,49] DFS: Disease-free survival; OS: Overall survival. 10.…”
Section: Tumor Suppressor Lncrnasmentioning
confidence: 99%
“…The diagnostic ability of ncRuPAR to differentiate GC from benign disease was further investigated based on the ROC curve analysis. The optimal cutoff value was 4.97, and AUC was up to 0.84 [24].…”
Section: Potential Clinical Application Of Lncrnas In Gcmentioning
confidence: 93%
“…Many novel studies demonstrated that AC096655.1-002 (also named gastric cancer-associated transcript 1 (GACAT1)), ncRuPAR, AA174084, FER1L4, GAS5, GACAT2 and AC138128.1 were significantly down-regulated in GC tissues [24,[28][29][30]32,37,101], while GACAT3, LINC00152, HULC, SUMO1P3, ABHD11-AS1, HOTAIR, PVT1, and GAPLINC were substantially up-regulated in GC tissues [21,25,26,31,35,36,61,102].…”
Section: Potential Clinical Application Of Lncrnas In Gcmentioning
confidence: 99%